Sociocultural Based Islamic Education at School in Rural Communities, South Sumatra - Suroso Suroso; Ahmad Suradi; Ani Aryati (STAI Hubbulwathan Duri, 2022)
Socio-cultural values that prioritize the formation of noble characters are gradually starting to be considered incompatible with the times, students are more fond of popular culture presented by various media available in the community. In fact, each region has a rich culture that can be developed to become the basis for character education for students in the area. The method used in writing this article is a qualitative method, using a phenomenological approach. The respondents in this study were teachers, community, local government in rural communities. To obtain data, the authors used interviews and observations at the research site. Social and cultural changes in society can affect the educational process as a result of a shift in the educational paradigm, such as changing the way of life, ways of learning, ways of communicating and thinking and others. The process of Islamic education in rural communities schools of South Sumatra must improve by changing the paradigm of sociocultural-based education in order to answer the demands of the times. In addition, Islamic education in schools must develop the values of peace, tolerance, human rights, democracy and justice. Educators in certain ethnic-religious-based schools should teach universal human and justice values that uphold the values of peace. Islamic education in schools with a sociocultural basis must teach students about universal religious values. Educators must teach and instill religious and cultural values that are friendly to differences, non-violence, uphold peace, and justice.